Difficulties in Diagnosing Pulmonary Nodular Lymphoid Hyperplasia - I. D. Lagkueva; O. P. Bliznyukov; N. V. Chernichenko; M. M. Dzhigkaeva; Ya. Yu. Murzin (Туберкулез и болезни лёгких)
The article presents a rare case of verified pulmonary nodular lymphoid hyperplasia (PNLH) in a 49-year-old man with history of chemotherapy and radiation therapy for stage 3B Hodgkin lymphoma with metastases in peripheral lymph nodes and the spleen. It describes computed tomographic semiotics of PNLH and the histological signs of the specimens collected during surgical treatment.